2020
DOI: 10.1038/s41467-020-19211-z
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules as potent biphasic modulators of protein liquid-liquid phase separation

Abstract: Liquid-liquid phase separation (LLPS) of proteins that leads to formation of membrane-less organelles is critical to many biochemical processes in the cell. However, dysregulated LLPS can also facilitate aberrant phase transitions and lead to protein aggregation and disease. Accordingly, there is great interest in identifying small molecules that modulate LLPS. Here, we demonstrate that 4,4’-dianilino-1,1’-binaphthyl-5,5’-disulfonic acid (bis-ANS) and similar compounds are potent biphasic modulators of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 72 publications
7
105
0
Order By: Relevance
“…The dynamics of interactions between GRN-2 and PrLD investigated here have furthered our understanding of the possible mechanisms by which GRNs could modulate intracellular inclusions of TDP-43. Complex coacervation of TDP-43 with RNA has been known to be an electrostatically driven process (Babinchak et al, 2020;Lim et al, 2016). In a similar vein, we showed that coacervation with GRNs is likely driven by net charges on the protein (Bhopatkar et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The dynamics of interactions between GRN-2 and PrLD investigated here have furthered our understanding of the possible mechanisms by which GRNs could modulate intracellular inclusions of TDP-43. Complex coacervation of TDP-43 with RNA has been known to be an electrostatically driven process (Babinchak et al, 2020;Lim et al, 2016). In a similar vein, we showed that coacervation with GRNs is likely driven by net charges on the protein (Bhopatkar et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…Disordered proteins enriched in one kind of charge will repel one another preventing self-coacervation but interaction with a partner containing counter-charge would minimize repulsion and promote LLPS (Pak et al, 2016). These interactions are also observed to be the driving forces behind the self-and complex-(with RNA) coacervation of TDP-43 (Babinchak et al, 2020;Conicella, Zerze, Mittal, & Fawzi, 2016;Li, Chiang, Chou, Wang, & Huang, 2018). However, the molecular determinants of heterotypic phase transitions of TDP-43 involving ligands vary depending on the partners and are still being discerned (Babinchak et al, 2020).…”
Section: Grn-2 Modulates the Phase Transitions Of Prld In Vitromentioning
confidence: 99%
“…hnRNPA1 CTD is more positively charged at acidic pH compared to higher pH, and our data suggest that some positive charges on hnRNPA1 CTD favor LLPS, potentially via ionic interactions with salts and polyanions, and allow for tuning via electrostatic forces. We acknowledge that other solution conditions (e.g., the presence of osmolytes) as well as inter‐ and intramolecular forces beyond electrostatic interactions also drive phase separation and should not be disregarded 33–35 . Overall, LLPS is a complex phenomenon whose mechanisms and regulation deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…CR can be used to identify both gel-like and solid-like amyloid states in the phase-separated materials. 33,34 CR uorescence was detected only aer the addition of PEG to both M237I p53C and wt p53C, showing the formation of aggregated structures and suggesting a solid state (Fig. 8a and b).…”
Section: Effects Of Polyanions On Phase Separation and Phase Transition Of P53mentioning
confidence: 99%